Research of Ship Deck Mechanisms Electric Drives Start by the Help of Soft Starters - Abdullayev, Y.R.; Sultanov, E.F.; Mammadov, E.M. (Herald of Azerbaijan Engineering Academy, 2021)
The issues of asynchronous electrical motors starters applied in ship deck mechanisms electric drives by the help of soft starting means were researched and noted the advantages of this method. Including, were indicated the advantages of using the soft starters means in asynchronous electric drives of deck mechanisms in raising of control system reliability and decreasing of electrical energy consumption. Starting into ship deck mechanisms electric drives work is usually performed by engine stators windings from the diagram “star” on the diagram “triangle”. This method of starting is not considered as sufficiently reliable. Besides of this, results of held analysis showed, that at the time of passage the transitional processes in these electric drives the magnitude of stators windings starting currents exceeds par in 5-7 times, but the magnitude of rotating moment on a shaft constitutes 150-200% from the par value. This in its turn, leads the precocious failure of engine mechanical elements and flop of supply network voltage. Considering the above for controlling by asynchronous motor with short-circuited rotor were considered the connectivity issues of the main starter to its stator winding. In view of the, in ships with level of automation AUT 2 control existing systems can’t answer to modern requirements and also with the aim of raising the reliability of work and energy-consuming decrease, it was suggested the using of device of the main starters in operating electric drives of deck mechanisms.